2012
DOI: 10.1002/pmic.201100563
|View full text |Cite
|
Sign up to set email alerts
|

History of protein–protein interactions: From egg‐white to complex networks

Abstract: Today, it is widely appreciated that protein-protein interactions play a fundamental role in biological processes. This was not always the case. The study of protein interactions started slowly and evolved considerably, together with conceptual and technological progress in different areas of research through the late 19th and the 20th centuries. In this review, we present some of the key experiments that have introduced major conceptual advances in biochemistry and molecular biology, and review technological … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
166
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 248 publications
(168 citation statements)
references
References 276 publications
(285 reference statements)
1
166
0
1
Order By: Relevance
“…Thus, identification of PPIs is critical to understanding the protein functions. Over the past few decades, many experimental techniques, such as yeast two-hybrid systems (Y2H) [4], mass spectrometry (MS) [5], tandem affinity purification (TAP) [6], and protein chip [7], have been developed to detect PPIs. These experimental approaches have provided an enormous amount of PPI data, which have facilitated the development of PPI databases such as IntAct [8], BioGRID [9], and HPRD [10].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, identification of PPIs is critical to understanding the protein functions. Over the past few decades, many experimental techniques, such as yeast two-hybrid systems (Y2H) [4], mass spectrometry (MS) [5], tandem affinity purification (TAP) [6], and protein chip [7], have been developed to detect PPIs. These experimental approaches have provided an enormous amount of PPI data, which have facilitated the development of PPI databases such as IntAct [8], BioGRID [9], and HPRD [10].…”
Section: Introductionmentioning
confidence: 99%
“…Finally it is worth mentioning that complex networks emerge not only in power grids and other human-made systems-including Internet [129,130], the topology of web pages (where the nodes are individual webs and edges are hyperlinks) [57,62], airline routes [131], electronic circuits [132] or socioeconomic systems [133]-but also in systems stemming from Nature, e.g., evolution [134], metabolic networks [135], protein interactions [136] and food webs [137]. For more details regarding the description and bibliographic references of these complex networks, which are outside the scope of this paper, we refer the interested reader to the recent books [62,90].…”
mentioning
confidence: 99%
“…Protein-protein interactions (PPIs) are fundamental to biology 1 and are tightly regulated via spatiotemporal mechanisms across many time and length scales. Studies on cell signaling on the cell membrane, for example, have revealed dynamic, nanoscale spatial compartments that facilitate specific PPIs and cellular processes 2 .…”
Section: Introductionmentioning
confidence: 99%